PENERAPAN PENGGUNAAN QRIS KEPADA PELAKU UMKM DI DESA LEKIS REJO DALAM MENINGKATKAN EFESIENSI TRANSAKSI DIGITAL - Mutmainah, Aura Cahya; Utami, Selvi Rinda; Wahyudi, Ovan; Putra, Rizky Septian; Gusvika Juzen, Ibra Falzan; Novitasari, Dian (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
The development of digital payment systems has become a necessity for micro, small and medium enterprises (MSMEs) to compete in the digital era. This community service activity aimed to provide training on creating and using Quick Response Code Indonesian Standard (QRIS) for UMKM actors in Lekis Rejo Village. The training method involved theory presentation, direct practice of QRIS registration, and mentoring on its implementation in daily business operations. Results showed that participants gained comprehensive understanding of QRIS benefits, successfully registered their businesses for QRIS, and implemented digital payment systems that improved transaction efficiency. Post-training evaluation indicated increased customer satisfaction due to more flexible payment options and improved financial record-keeping. This activity demonstrates that proper training can accelerate digital transformation among rural MSMEs, ultimately supporting business sustainability and competitiveness.